A revision and addition to Zopheridae (Coleoptera: Tenebrionoidea) in Baltic amber: possible connections between modern Holarctic distributions and Eocene ‘amber forests’ - Alekseev, Vitalii; Mckellar, Ryan C.; Bukejs, Andris (Zootaxa, 2024)
One new extinct genus and six new extinct species of Zopheridae are described and illustrated from Eocene Baltic amber: Usechus andrushchenkoi Alekseev et Bukejs sp. nov., Coxelus carstengroehni Alekseev et Bukejs sp. nov., Paha vanivanitatum Alekseev et Bukejs sp. nov., Lasconotus tenebrisilvarum Alekseev et Bukejs sp. nov., Helioctamenus groehni Alekseev et Bukejs sp. nov., and Thanatoplagia tamutisi Alekseev et Bukejs gen. et sp. nov. These described taxa include the first fossil representatives of five extant genera and two extant tribes of the family Zopheridae. The assumed paleoecology of these taxa within the amber-producing forest paleohabitat, as well as zoogeography of new fossils are discussed. In addition, new fossil records of Xylolaemus legalovi Alekseev et Bukejs, 2016, X. richardklebsi Alekseev et Bukejs, 2016, Endophloeus gorskii Alekseev et Bukejs, 2016, Yantaroxenos colydioides Nabozhenko, Kirejtshuk et Merkl, 2016, and Zopheromimus auriborussiensis Alekseev et Nabozhenko, 2023 from Baltic amber are presented. A catalogue of Zopheridae described from Baltic amber (currently 19 species within 16 genera) is compiled herein, and an identification key for all taxa is provided. The zoogeographical affinities of the Baltic amber zopherid assemblage are assessed. The present-day disjunct distributions of the zopherid genera that have survived since the Eocene and are currently present in the Holarctic region probably resulted from a uniform fauna in the warm temperate regions of the Northern Hemisphere in the first half of the Paleogene. This uniform fauna was followed by independent reduction of distributions within four regions (West Palearctic, East Palearctic, West Nearctic, and East Nearctic). The ‘circum-Arctic quadrants’ schema is proposed for visualisation of this hypothesis. Additionally, a zonal middle to late Eocene ‘amberiferous ring’ is hypothesized as a probable migration pathway for several zopherids in this part of the Eocene. This ‘ring’ is a belt of amber-producing forests in the Northern Hemisphere, with the potential to preserve a wider distribution of taxa that relied on mixed conifer-fagacean forests similar to the Baltic amber forest flora and its faunal assemblage.